PENINGKATAN KETERAMPILAN USAHA PRODUKSI MEDIA PENDIDIKAN MAHASISWA PROGRAM STUDI TEKNOLOGI PENDIDIKAN MELALUI PROGRAM MAGANG KEWIRAUSAHAAN DI PT. MATARAM INDAH - Haryanto, Haryanto (Universitas Negeri Yogyakarta, 2003)
The purpose of this program is to improve: (a) the knowledge of entrepreneurship ineducational media· production, (b) technical skill in education media production, (c) entrepreneurial motivation, and (d) to develop collaborative networking with small industry in educational media production.The internship program conducted through experiental learning. In this programstudents involved in the real process of media production and entrepreneurship. There are from activities: (a) Preparation. This activity is intended to give information about the process of entrepreneurship and educational media production, (b) Internship. In this activity students involve and learn the real process of entrepreneurship and production of educational media. (c) Evaluation. This activity is intended to evaluate the process and result of the program.The result of this program are: (a) 90% of students motivated to involve in industry of educational media, (b) 100% of students is able to make design of educational media in which each of them have one design, (c) The industry want expand and continue of the program in the next time, d) The lecturer know more about the real learning and model of teaching.Key words: educational media, and enterpreneurship internship.